The Representive of Metric Projection on the Finite Codimension Subspace in Banach Space (Communications in Mathematical Research, 2021)
In the paper we introduce the notions of the separation factor $κ$ and givea representive of metric projection on an $n$-codimension subspace (or an affine set)under certain conditions in Banach space. Further, we obtain the distance formulafrom any point $x$ to a finite $n$-codimension subspace. Results extend and improve thecorresponding results in Hilbert space.
Keywords: $n$-codimension; separation factor $κ$; weakly completely separated.